2020
DOI: 10.1155/2020/5847478
|View full text |Cite
|
Sign up to set email alerts
|

Association of Brain-Gut Peptides with Inflammatory Cytokines in Moyamoya Disease

Abstract: Systemic inflammation has been shown to play a pivotal role in the pathogenesis of moyamoya disease (MMD). Brain-gut peptides exhibit regulatory effects in the secretion of proinflammatory cytokines. To investigate the association between brain-gut peptides and inflammation in the occurrence of MMD, 41 patients with MMD, as well as 74 age- and sex-matched healthy individuals were enrolled. The levels of four brain-gut peptides (vasoactive intestinal polypeptide (VIP), cholecystokinin (CCK), somatostatin (SST),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…Moyamoya disease (MMD) was first defined by Suzuki and Takaku in 1999( 1 ) and presents as the presence of an abnormal vascular network at the base of the brain. MMD is characterized by progressive stenosis and even occlusion of the terminal portion of the bilateral internal carotid and intracerebral arteries ( 2 ). The most common symptoms of MMD include headache, ischemia and hemorrhage ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moyamoya disease (MMD) was first defined by Suzuki and Takaku in 1999( 1 ) and presents as the presence of an abnormal vascular network at the base of the brain. MMD is characterized by progressive stenosis and even occlusion of the terminal portion of the bilateral internal carotid and intracerebral arteries ( 2 ). The most common symptoms of MMD include headache, ischemia and hemorrhage ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that the expression levels of periphery inflammatory factors in MMD were higher than those in HCs, including TNF-α, IL1-β, IL-6, etc. (28,29). The microenvironment formed by abnormally secreted inflammatory factors may promote the proliferation and angiogenesis of cells in affected vessels (30).…”
Section: Discussionmentioning
confidence: 99%
“…Some researches manifest that MMD could be the result of vascular immune injury and inflammation response ( 2 , 30 ). Recent studies of our team have found that the upregulated expressions of various plasma inflammatory factors, such as IL-1β, IL-12, and TNF-α, in patients with MMD suggested that inflammation might regulate the process of MMD ( 31 ). Inflammatory response ultimately leads to the hyperplasia of intimal vascular smooth muscle cells and neovascularization by proliferation of endothelial cells, that motivates lumen stenosis and collateral formation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%